PREDICTIVE FACTORS OF BLOOD TRANSFUSION AFTER TURP AT SARDJITO GENERAL HOSPITAL YOGYAKARTA - Arifin, Bobbi; Tranggono, Untung (Indonesian Urological Association, 2017)
Objective: To know the factors that can predict the need for blood transfusions after transurethral resection of the prostate (TURP) at Dr. Sardjito General Hospital. Material & method: This is a retrospective study. Analysis performed on 250 patients who underwent TURP between the years 2013 to 2015. The independent variables evaluated were age, body mass index (BMI), the estimated size of the prostate by transabdominal ultrasonography (TAUS), duration of surgery, hemoglobin level (Hb), the value of international normalized ratio (INR), history of hypertension, diabetes mellitus (DM) and the use of aspirin, and leukosituria. The dependent variable evaluated was the estimated amount of bleeding which was described by the blood transfusion requirements in patients after TURP. Results: Hb levels before surgery (p=0.000), history of hypertension (p=0.001) and a history of aspirin consumption (p=0.008) had a significant association with blood transfusion after TURP. The Hb cut-off value was 12.45 g/dl. Age, BMI, the estimated size of the prostate by TAUS, duration of surgery, history of diabetes and leukosituria did not have a significant association with blood transfusion after TURP. Conclusion: The results showed that Hb levels before surgery, a history of hypertension and aspirin usage can be predictive factors for blood transfusions after TURP.